RETRACTED ARTICLE: Inhibition of PAD4 enhances radiosensitivity and inhibits aggressive phenotypes of nasopharyngeal carcinoma cells - Hao Chen; Min Luo; Xiangping Wang; Ting Liang; Chaoyuan Huang; Changjie Huang; Lining Wei (Cellular & Molecular Biology Letters)
Abstract Background Nasopharyngeal carcinoma (NPC) is a tumor deriving from nasopharyngeal epithelium. Peptidyl-arginine deiminase 4 (PAD4) is a vital mediator of histone citrullination and plays an essential role in regulating disease process. Radiotherapy is an essential method to treat NPC. In this research, we explored the effect of PAD4 on NPC radiosensitivity. Methods We enrolled 50 NPC patients, established mice xenograft model, and purchased cell lines for this study. Statistical analysis and a series of experiments including RT-qPCR, clonogenic survival, EdU, Transwell, and wound healing assays were done. Results Our data manifested that PAD4 (mRNA and protein) presented a high expression in NPC tissues and cells. GSK484, an inhibitor of PAD4, could inhibit activity of PAD4 in NPC cell lines. PAD4 overexpression promoted the radioresistance, survival, migration, and invasion of NPC cells, whereas treatment of GSK484 exerted inhibitory effects on radioresistance and aggressive phenotype of NPC cells. Additionally, GSK484 could attenuate the effect of PAD4 of NPC cell progression. More importantly, we found that GSK484 significantly inhibited tumor size, tumor weight and tumor volume in mice following irradiation. Conclusions PAD4 inhibitor GSK484 attenuated the radioresistance and cellular progression in NPC.